Предмет: Математика, автор: ilyasseven

Упростите выражение. Решите примерчик

Приложения:

Ответы

Автор ответа: Аноним
1
(1-cosa)(1+cosa)*ctg²a=(1-cos²a)*ctg²a=sin²a*cos²a/sin²a=cos²a
Автор ответа: wangross
1
(1+cos \alpha )\cdot ctg^2 \alpha \cdot(1-cos \alpha )=(1+cos \alpha )(1-cos \alpha )\cdot ctg^2 \alpha = \\ \\ =(1-cos^2 \alpha )\cdot ctg^2 \alpha =sin^2 \alpha \cdot ctg^2 \alpha =sin^2 \alpha \cdot \frac{cos^2 \alpha }{sin^2 \alpha } = \frac{sin^2\alpha\cdot cos^2 \alpha  }{sin^2 \alpha }  = \\  \\ =cos^2 \alpha
Похожие вопросы